David and Solomon in the Portal of Paradise: A Moral Reflection Seen through the Old Testament in Ourense Cathedral (13th C.) - Conde Cid, Natalia (Madrygal. Revista de Estudios Gallegos, 2016)
The Portal of Paradise of Ourense Cathedral is essentially an area with a penitential function. It offers a visual frame that helps the faithful “sinner” make a sincere act of contrition before crossing the gate of the temple, which supposedly represents Christ himself according to the text of St. John 10, 9-10. Here one can find the statues of David, Solomon and nine prophets, which give it a remarkable moralizing character within the penitential context created at the Fourth Lateran Council of 1215, which was undoubtedly written down in the early thirteenth century in the Tractatus de Poenitentia by the Bishop of Ourense Don Lorenzo.
Keywords: Middle Ages; Old Testament; Penance; Bishop Lorenzo; Portal of Paradise; Ourense Cathedral.